DIAGNOSTICS AND TREATMENT FAILS OF COMMUNITY-ACQUIRED PNEUMONIA IN HOSPITAL - Фуштей І. М.; Савченко О. О.; Подсевахіна С. Л.; Ткаченко О. В. (World of Medicine and Biology, 2014)
Pneumonia is one of the common diseases that are often found in the practice of general practitioner. Diagnosis and treatment of pneumonia in our country has developed clinical guidelines, which aim to improve the prognosis in this disease [1,2]. However, clinical practice shows that these recommendations often remain unfulfilled and doctors admit many fails, both in diagnosis and in treatment of this disease [3,4]. At the same time, there is evidence that if a doctor should be current guidelines, the percentage of treatment failure is reduced by 35-40% [5]. The aim of research Examine the implementation of national recommendations for treatment and diagnosis of community-acquired pneumonia (order number 128 of 2007.) In clinical practice. Materials and methods The analysis of 100 records of patients treated for community-acquired pneumonia in the hospital MI "Central District Hospital of Ordzhenikidzevskiy district of Zaporozhye" was held. Results Analysis of case histories showed that in most cases the diagnosis of pneumonia was made only after X-ray examination. To obtain data X-rays of the chest or are diagnosed with acute respiratory infections (35%) or patients treated independently from the "cold" (43%), only 22% of cases of pneumonia was suspected on the basis of the clinic. According to our survey data, 80% of hospitalized patients had indications for hospitalization and could be treated on an outpatient basis. Analysis of the starting antibiotic therapy in the hospital showed that in 93% of cases the primary antibiotic regimens in all community-acquired pneumonia in the hospital was ceftriaxone. In 83% of patients receiving respiratory or fluoroquinolone antibiotic as seed (29%) or after treatment with a macrolide (54%), which promotes resistance S. pneumonia. The recommended speed antibacterial therapy of pneumonia in the hospital, according to our data, in practice, is not carried out. Treatment time is often overstated. In terms of the recommended antibiotic therapy was completed in only 10% of patients, 16% of the treatment time exceeds 14 days. In addition to antibiotic therapy, patients often received: probiotics (62%), antifungal drugs (32%), serratiopeptidase (42%), multivitamins (36%). These drugs do not have evidence of its effectiveness in the treatment of community-acquired pneumonia. Conclusion The results of our study showed that the clinical practice of diagnosis and treatment of community-acquired pneumonia differs significantly from the current guidelines: all patients hospitalized with community-acquired pneumonia, regardless of severity, too often used in the treatment of cephalosporins III generation, respiratory fluoroquinolones, very rarely used protected aminopenicillins, overstated timing of antibiotic therapy, not the principle of sequential therapy, there is a polypharmacy and use non-antibiotic drugs without evidence of its effectiveness.